Evaluation and optimization of ecological compensation fairness in prefecture-level cities of Anhui province. (1st March 2023) - Wang, Sufeng; Li, Shourong; Jiao, Jianling
Abstract: Scientific evaluation and continuous optimization of the fairness of ecological compensation are conducive to improving the effect of air pollution control. However, relevant research in this field is in its infancy. Based on the data on urban-scale PM2.5 concentration and ecological compensation from the third quarter of 2018 to the fourth quarter of 2020, this study takes 16 prefecture-level cities in Anhui Province as the research area and uses the Granger causality test to determine the PM2.5 overflow paths of each city. Moreover, using 2020 as an example, the PM2.5 spillover effect of each city is calculated, and the haze Gini coefficient of Anhui Province is obtained. According to the empirical results, the ecological compensation policy for PM2.5 control in Anhui Province is in a relatively equal fairness range (0.295). On this basis, combined with the scatter diagram of ecological compensation and spillover effect, it is suggested to reduce the ecological compensation of five cities, including Maanshan and Xuancheng, while the ecological compensation of the remaining 11 cities should be increased. Two feasible optimization schemes, i.e., annual adjustment and regular adjustment, are proposed for environmental regulators to choose.